2020
DOI: 10.1071/an18759
|View full text |Cite
|
Sign up to set email alerts
|

Carcass and meat quality of crossbreds of Thai indigenous chickens and Rhode Island Red layer chickens as compared with the purebreds and with broilers

Abstract: Context In order to maintain the availability of meat from indigenous chicken types in remote Asian regions with their special meat quality, novel ways of increasing efficiency are needed. One way could consist of crossbreeding with layer type chickens that are genetically quite distant from indigenous breeds. Aim The three hypotheses tested were as follows: that the meat quality of indigenous chickens differs from that of broilers; that the meat quality of male layer chickens resembles that of indigenous chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 39 publications
3
12
0
2
Order By: Relevance
“…They also demonstrated lower abdominal fat in Ross broilers as compared with RIR layers. In this study, the dressing percentage in broilers chickens (72.1%) was quite near to that reported in other studies ( 24 , 25 ). At the same age, the dressing percentage in spent hens (69.3 %) was close to that reported in Mos spent hens (69.8 %), but higher than that of ISA Brown spent hens (63.0 %) ( 26 ).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…They also demonstrated lower abdominal fat in Ross broilers as compared with RIR layers. In this study, the dressing percentage in broilers chickens (72.1%) was quite near to that reported in other studies ( 24 , 25 ). At the same age, the dressing percentage in spent hens (69.3 %) was close to that reported in Mos spent hens (69.8 %), but higher than that of ISA Brown spent hens (63.0 %) ( 26 ).…”
Section: Discussionsupporting
confidence: 84%
“…The fat content of the spent hens was definitely higher, as evidenced by the percentage of abdominal fat (almost four times). Similarly, Kaewkot et al ( 25 ) found that RIR chickens had much ( P < 0.05) abdominal fat than the Ross broiler chickens. In contrast, research by Tang et al ( 17 ) and Mueller et al ( 24 ) indicated that the proportion of abdominal fat in laying hens was much lower than that of indigenous chickens.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Oral administration of a fecal suspension from the Beijing-You broilers decreased the drip-loss rate of the Arbor Acres broilers, suggesting the gut microbiota derived from native broilers could be used to improve the meat quality of commercial breeds. Compared to commercial broilers, some studies have shown that native broilers have lower drip-loss rates and longer muscle fiber diameter ( 3 , 44 , 45 ). Consistent with these reports, our data show that oral fecal microbes decreased drip loss and an increased biceps femoris muscle fiber diameter of the Arbor Acres broilers, suggesting that certain muscle characteristics may be influenced by the gut microbiota from native broilers to commercial broilers.…”
Section: Discussionmentioning
confidence: 99%
“…TR to eggs was calculated using the same feed intake and egg composition than previously presented. The calculation of BCFs in hen muscle was based on a fat content of 10% in the fresh matter according to Kaewkot et al (2020).…”
Section: Selection Criterion Of Articles In the Datasetmentioning
confidence: 99%